Formation Of Student’s Religious Character Throught Dzikir And Sholawat Assembly At Universitas Islam Balitar (UNISBA) Blitar - winarto, winarto; Sodiq, Mohammad; Nurlatifah, Siti; Zahria, Linta (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
The current globalization has led Indonesian society to distort the nation’s character education. In fact, character education is a very important foundation of the nation and needs to be instilled early in chiidren, as well as in adolescents who are stepping into adulthood. The current changing conditions encourage students to have high and strong religiosity. With a strong religiosity, students can become a strong person who is not easily swayed by changing times. The Dzikir and Sholawat assembly at UNISBA , apart from being a medium for Dzikir and a medium for student character devalopment, is expected to be a medium for strengthening the religious character of students. The difference in attitude between students shows the difference between those who follow regularly and those who never follow at all. Therefore, one of the Applications is throught religious character building throught the Dzikir and Sholawat assembly for Students at UNISBA Blitar. A greet nation does not only rely on natural resources, but must also be supported by human resources that have a strong characte. Human resources will contribute to realizing the dignity of the nation. Globalization that is sweeping the nation today encourages people to have poor character. The impact of globalization with a relatively fast time causes culture to change completely. In the above case, character becomes very important in fortifying the nation’s generation to have a good personality. So that research on the formation of religious character in the nation’s next generation more narrowly in students is seen as very critical to be studied and researched compreshensively. This research will try to find the formation of religious character through the Dzikir and Sholawat assembly of UNISBA Blitar. This research uses a case type skinative approach. Data analysis using Kut Lewi’s 3-step theory.